Perancangan Strategi Promosi Destinasi Wisata Alam Taman Kopi Guntang Bersama Fujifilm Untuk Keluarga Muda Di Kota Bandung - Putra Adrianto, Rizky; Wiba Pamela, Apsari; Muthmainnah, Ligar (Universitas Telkom, 2024)
Taman kopi guntang is a new tourist destination located within the Mount Puntang natural tourist area. Visitors can enjoythe cool air because the tourist spot is surrounded by lots of plants and trees. Visitors can also enjoy the beautiful viewsof Mount Puntang. Taman kopi guntang is located in Campaka Mulya Village, Cimaung District, Bandung Regency. Tamankopi guntang is managed directly by the Bandung City Forestry Company. Taman kopi guntang is a one stop destinationand has a coffee shop, villa, glamping and camping ground which is one of the main destinations for visitors. If you lookat the problem of the Taman kopi guntang, there is still a lack of awareness that has not been formed. The designer usedqualitative research methods and carried out observation techniques, questionnaires, interviews with the management ofTaman kopi guntang and the target audience. It is hoped that by designing creative media such as photobooths, touristscan get free vouchers for a staycation with their family by taking the most exciting photos using a photobooth and uploadingthem to social media then tagging @tamankopiguntang and @fujifilm, this promotional media can be used and is useful forthe management of Taman kopi guntang in its development and in the future . Taman kopi guntang Tourism is for men andwomen aged 28 – 35 years who enjoy outdoor activities, are interested in natural beauty, can increase togetherness withfamily, enjoy chatting with family, have comfortable trips with family and immortalize moments with family